Pengembangan Agroeduwisata di Desa Pagarawan, Kabupaten Bangka Berdasarkan Partisipasi Masyarakat - Tiara Millenia Loziska; Sabrina Alifia Zahra; Danindra Atharikusuma (Arsir: Jurnal Arsitektur, 2024)
Developing tourism villages with the concept of agroedutourism is one of the efforts to improve regional competitiveness. Pagarawan Village, Bangka Regency, has excellent potential to be developed as an agroedutourism village. This study aims to determine the development of agroedutourism in Pagarawan Village based on community participation. This research uses a qualitative method with a case study approach. Primary data was obtained through observation, interviews, and documentation. The results showed that the development of agroedutourism in Pagarawan Village is based on active participation from the community. This participation provides concrete benefits to the community, such as increased knowledge about agriculture and fisheries and increased income. The development of agroedutourism in Pagarawan Village is carried out by maximising the potential possessed by the village, such as its main tours, namely, oyster mushroom cultivation, freshwater fish farming, mangrove crab farming, and hydroponics. The supporting tours are fishing areas, culinary areas, outbound areas for children, lazy river areas, and water sports. The site can be developed into several activity spots prioritising the agriculture, fisheries, community, education, and tourism sectors. To make the tourism village sustainable, it requires active participation from the surrounding community in development and management and support from the local government.